PERMINTAAN PEMBIAYAAN MURABAHAH BERDASARKAN TINGKAT INFLASI DAN SUKU BUNGA BI RATE PADA BANK SYARIAH DI INDONESIA - Jibril, Hadira Thumaninah; Ardiansyah, Ardiansyah; Kaluge, David; Karim, Kasnaeny (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2019)
This study aims to analyze the level of murabahah financing that influences by the inflation rate and BI rate at sharia banks in Indonesia in 2013-2016. This research is a quantitative descriptive study. Data were analyzed using multiple linear regression analysis. The results showed that, partially, inflation has a positive significant effect murabahah financing. However, the BI rate has no significant effect on murabahah financing in sharia banks in Indonesia in 2013-2016. Simultaneously, inflation and BI rate had a significant effect on murabahahfinancing in sharia banks in Indonesia in 2013-2016. Therefore, the management of sharia banks in Indonesia should be more active in introducing sharia funding to society.